Abrasive waterjet cutting of aluminum alloys: Workpiece surface roughness - Tosun, Nihat; Dagtekin, Ihsan; Ozler, Latif; Deniz, Ahmet (My University, 2013)
Abrasive waterjet machining is one of the non-traditional methods of the recent years which found itself a wide area of application in the industry for machining of different materials. In this paper, the surface roughness of 6061-T6 and 7075-T6 aluminum alloys are being cut with abrasive waterjet is examined experimentally. The experiments were conducted with different waterjet pressures and traverse speeds. It has been found that the surface roughness obtained by cutting material with high mechanical properties is better than that of obtained by cutting material with inferior mechanical properties. © (2013) Trans Tech Publications, Switzerland.
2nd International Symposium on Manufacturing Systems Engineering, ISMSE 2013 -- 27 July 2013 through 29 July 2013 -- 100433
Keywords: Aluminum; Surface roughness; Waterjet